Reliability of platinum electrodes and heating elements on SiO2 insulation layers and membranes. Issue 9 (August 2015) - Rusanov, R.; Rank, H.; Graf, J.; Fuchs, T.; Mueller-Fiedler, R.; Kraft, O.
Abstract: In this work, failure mechanisms of Pt electrodes including adhesion problems, material migration due to thermally induced compressive stress and electromigration that could occur in the platinum electrodes and heater structures at temperatures above 600 °C have been systematically studied, after the deposition. Lifetime determination, scanning electron microscopy and XRD analysis have been applied for samples which have experienced different loading conditions in order to qualitatively and quantitatively understand the phenomena. Electromigration testing is performed with the aim to enable time-to-failure prediction for sensor elements and compare different platinum layers in terms of their stability. Dedicated, application-related test structures are used so that the results are applicable to sensor lifetime estimations. Furthermore, a method for the determination of thermal conductivity of thin insulating films has been adapted for the characterization of plasma-enhanced chemical vapor deposition (PECVD) silicon oxide and successfully applied on two materials with different deposition recipes. These two materials are used for the fabrication of platinum-based heating elements with PECVD SiO2 as insulation or membrane layer. The results for the two recipes are similar but with a significant difference. A slight increase of the conductivities has been observed due to a thermal anneal of the test structures at temperatures above 700 °C. Highlights: Reliability and resistivity of Pt electrodes and heater elements have been studied. XRD analysis has been performed on as deposited and differently annealed Pt layers. Parameters of Black's equation for electromigration failure of various Pt layers The thermal conductivities of PECVD SiO2 thin-films are determined for up to 450 °C. Pt delamination in the test structures affects thermal conductivity measurements.